The Role of Lycium barbarum (Goji Berry) in Apoptosis and Autophagy in the Experimental Ulcerative Colitis Model - Cimen, Bue thorn ra; Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Baspinar, Serpil; Tan, Fatih; Ozercan, Ibrahim Hanifi (Springer, 2024)
Ulcerative colitis is one of the most common intestinal diseases in the world. Lycium barbarum (Goji Berry) is a type of fruit that is frequently used in alternative medicine, with antioxidant, antimicrobial, anti-aging, and anti-inflammatory effects. Although the effect of Lycium barbarum (LB) on intestinal diseases has been extensively studied, the mechanism of action on apoptosis and autophagic pathways in the ulcerative colitis model has not yet been fully elucidated. In this study, the effect of LB on the apoptosis and autophagy pathways in the ulcerative colitis model was investigated. Wistar albino male rats were used in the study. DSS chemical was used to create an ulcerative colitis model and LB was used to prevent colitis formation. In our study, in the LB+DSS group compared to the DSS group, wherein it was determined that p53 and Beclin 1 protein levels increased, TIGAR protein level decreased, MDA levels decreased, GSH level and catalase activity increased. Also, in the histopathological results, ulcerative colitis did not occur in the LB+DSS group. In general, our findings show that LB prevents the formation of ulcerative colitis, reduces damage, and activates the defense and apoptosis/autophagy mechanisms. When the results of our study are evaluated as a whole, we can say that LB has a promising potential to prevent ulcerative colitis.
Keywords: apoptosis; autophagy; DSS; Lycium barbarum (Goji Berry); ulcerative colitis